I reč Сěsarʹ: Titlo-abbreviations in Old East Slavic - Skjølsvold, Jens Kristian (UiT Norges arktiske universitet, 2023)
In this thesis I research the use of a diacritic mark know as a titlo and its use in Old East Slavic. Available literature suggests that titlos were used by Muscovite scribes to abbreviate words that denoted objects which were regarded as particularly sacred. However, literature on Old Rusian and Middle Russian handwriting, and Slavic paleography suggest that titlo-abbreviations may have been used to economize penmanship. In the simplest form, I ask, why did Old East Slavic scribes utilize titlos to abbreviate words? The paradigmatic approach of this thesis is drawn from Cognitive Linguistics, whereby I conduct a statistical analysis on data compiled from The Tromsø Old Russian and OCS Treebank (TOROT). The statistical analysis shows that neither the length of the word, nor the length difference between full form and abbreviated form determined whether a noun would be abbreviated by titlo. The result of the statistical analysis suggests that titlo-abbreviations are all about meaning, and that titlos were not used as a pragmatic diacritic in terms of efficiency. I attempt to infer the meaning of the most frequent titlo-abbreviated words, and further relate these words to another by contiguity based on the prototypical meaning of sacred. I also present a radial network of metonymic extensions from the prototypical meaning of sacred.